12 Lessons learned from the management of the coronavirus pandemic. Issue 6 (June 2020) - Forman, Rebecca; Atun, Rifat; McKee, Martin; Mossialos, Elias
Highlights: There have been diverse management strategies displayed in COVID-19 crisis response. 12 key lessons can guide adjustments to our crisis response strategies. These lessons can guide decisions to help reduce economic and social impacts. Transparency, decisive leadership, effective communication, solidarity, and accountability are vital. We can use innovative technologies and financing mechanisms in pandemic response. Abstract: The Coronavirus SARS-CoV-2 has spread rapidly since the first cases hit Wuhan, China at the end of 2019, and has now landed in almost every part of the world. By mid-February 2020, China, South Korea, Singapore, Taiwan, and – to some extent – Japan began to contain and control the spread of the virus, while conversely, cases increased rapidly in Europe and the United States. In response to the pandemic, many countries have had to introduce drastic legally mandated lockdowns to enforce physical separation, which are ravaging economies worldwide. Although it will be many months or even years before the final verdict can be reached, we believe that it is already possible to identify 12 key lessons that we can learn from to reduce the tremendous economic and social costs of this pandemic and which can inform responses to future crises. These include lessons around the importance of transparency, solidarity, coordination, decisiveness, clarity, accountability and more.